PENGARUH PENAMBAHAN VITAMIN C DAN EKSTRAK TEMULAWAK PADA PAKAN KOMERSIL TERHADAP PERTUMBUHAN POST LARVA IKAN PAPUYU (Anabas testudineus Bloch) - Heni Purwati; Herliwati Herliwati; Indira Fitriliyani (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2015)
Adding effect of vitamin C and extracts temulawak on this research aims to determine the effect of vitamin C on the feed premixes. The addition of ginger aims to increase appetite post of papuyu fish larvae and post larvae growth of papuyu fish reared in hapa. The usefulness of this research is to gain a level optimization of the use of vitamin C and extracts of ginger in immune papuyu post-larval fish, so we get a superior seed.From the research results that the addition of vitamin C and ginger did not affect growth, but significant effect on survival and feed conversion papuyu post-larval fish. Value retention of protein and good fats in treatment B (addition of vitamin C to commercial feed). The range of water quality in the research is still in a good range and allow the fish to live flowers papuyu.